Vam3, a derivative of resveratrol, attenuates cigarette smoke-induced autophagy - Shi Ji; Yin Ning; Xuan Ling-ling; Yao Chun-suo; Meng Ai-min; Hou Qi (Acta Pharmacologica Sinica, 2016)
Aim: To appraise the efficacy of Vam3 (Amurensis H), a dimeric derivative of resveratrol, at inhibiting cigarette smoke-induced autophagy. Methods: Human bronchial epithelial cells were treated with cigarette smoke condensates, and a chronic obstructive pulmonary disease (COPD) model was established by exposing male BALB/c mice to cigarette smoke. The protein levels of the autophagic marker microtubule-associated protein 1A/1B-light chain 3 (LC3), Sirtuin 1 (Sirt1), and foxhead box O 3a (FoxO3a) were examined using Western blotting and Immunohistochemistry. LC3 punctae were detected by immunofluorescence. The levels of FoxO3a acetylation were examined by immunoprecipitation. The level of intracellular oxidation was assessed by detecting ROS and GSH-Px. Results: Vam3 attenuated cigarette smoke condensate-induced autophagy in human bronchial epithelial cells, and restored the expression levels of Sirt1 and FoxO3a that had been reduced by cigarette smoke condensates. Similar protective effects of Vam3, reducing autophagy and restoring the levels of Sirt1 and FoxO3a, were observed in the COPD animal model. Additionally, Vam3 also diminished the oxidative stress that was induced by the cigarette smoke condensates. Conclusion: Vam3 decreases cigarette smoke-induced autophagy via up-regulating/restoring the levels of Sirt1 and FoxO3a and inhibiting the induced oxidative stress.